Formation and control of off-odors in aquatic processing products: a review - Hongliang Chen; Chaoyue Zhang; Yunhao Chang; Hongliang Liu; Haihong Chen; Bing Xu; Yi Wang; Wei Li; Xinhui Xing (Food Science of Animal Products, 2025)
Off-odors in aquatic products represent a critical quality concern for the aquatic food industry, severely compromising sensory attributes, consumer preference, and food safety due to potential health hazards. These undesirable odors result from a combination of mechanisms, including biochemical reactions and industrial processing, which collectively determine the final product quality. This comprehensive review methodically investigates four critical dimensions: 1) development mechanisms of off-odors, 2) compounds contributing to off-odors, 3) generation of off-odors, and 4) advanced deodorization methodologies. Special emphasis is placed on elucidating molecular-level interactions between off-odor compounds and proteins, as well as the characteristic biosynthesis patterns of off-odors observed across different tissue types in various aquatic species. Through a comprehensive analysis of the sources of off-odors and mitigation technologies, this review proposes a technical framework for the targeted reduction of off-odors in aquatic products, offering valuable insights for quality optimization in industrial applications.